Threats of Microplastic Pollution on Aquaculture Activities in Indonesia - Wicaksono, Ega Adhi (Torani Journal of Fisheries and Marine Science, 2022)
Aquaculture is a growing fisheries sector. Along with the growth of aquaculture, water quality problems become one of the main factors that need to be considered, especially related to pollution pressure. Microplastic (MPs) is a pollutant sourced from anthropogenic activities and is currently in the spotlight and has been widely studied in aquatic environments around the world. However, in Indonesia, research related to MP especially in term of aquaculture activities is still lacking. The presence of MP in aquaculture activities can originate from internal sources such as the use of unmaintained aquaculture equipment/facilities and the use of feed contaminated with MP. Then, the external source of MP at the cultivation location can come from water sources that come from an environment that has been previously polluted by MP. Maintenance of aquaculture equipment/facilities, search for alternative feed raw microplastic free materials and protection of the aquatic environment from MPs are some of the ways to reduce the presence of MP in aquaculture sites. The existence of MP in aquaculture activities is related to food safety of aquaculture commodities.